The emerging church : religion at the margins - Packard, Josh (Religion in politics and society., 2012)
If a church resists rules, rituals, and dogma, what holds it together? Josh Packard explores the inner workings of the Emerging Church, revealing how a movement that rejects organizational trappings and embraces a do-it-yourself ethic has managed to create a distinctive place for itself at the margins of mainstream Christianity. Packard demystifies the beliefs and operations of the loosely connected Emerging Church congregations that developed in direct response to the heavily bureaucratic megachurches. While acknowledging the challenges inherent in sustaining such a movement, he shows that the church succeeds not despite its anti-institutional approach, but because of it. His work offers new insights into the interplay of culture, organizations, and doctrine in today's religious landscape.